2022
DOI: 10.1007/s00271-022-00829-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimating crop coefficients and actual evapotranspiration in citrus orchards with sporadic cover weeds based on ground and remote sensing data

Abstract: Accurate estimations of actual crop evapotranspiration are of utmost importance to evaluate crop water requirements and to optimize water use efficiency. At this aim, coupling simple agro-hydrological models, such as the well-known FAO-56 model, with remote observations of the land surface could represent an easy-to-use tool to identify biophysical parameters of vegetation, such as the crop coefficient Kc under the actual field conditions and to estimate actual crop evapotranspiration. This paper intends, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…[1%] is the permanent wilting point (Morgan et al 2006;Ippolito et al 2022). The irrigation rates in the current experiment had two different rates for the 360 and 485 trees ha − 1 (78%-ET c , and 100%-ET c ), and the 920 trees ha − 1 irrigation rates (50%-ETc, 78%-ET c , and 100%-ET c ) corresponding to 31.4 L h − 1 , 48.5 L h − 1 , and 62.8 L h − 1 for 50%-ET c (de cit) 78%-ET c (moderate), and 100%-ET c (high /grower standard) emitters, respectively.…”
Section: Study Site Conditions and Treatmentsmentioning
confidence: 99%
“…[1%] is the permanent wilting point (Morgan et al 2006;Ippolito et al 2022). The irrigation rates in the current experiment had two different rates for the 360 and 485 trees ha − 1 (78%-ET c , and 100%-ET c ), and the 920 trees ha − 1 irrigation rates (50%-ETc, 78%-ET c , and 100%-ET c ) corresponding to 31.4 L h − 1 , 48.5 L h − 1 , and 62.8 L h − 1 for 50%-ET c (de cit) 78%-ET c (moderate), and 100%-ET c (high /grower standard) emitters, respectively.…”
Section: Study Site Conditions and Treatmentsmentioning
confidence: 99%
“…1. Estimating crop coefficients and actual evapotranspiration in citrus orchards with sporadic cover weeds based on ground and remote sensing data (Ippolito et al 2022) 2. Irrigation efficiency optimization at multiple stakeholders' levels based on remote sensing data and energy water balance modelling (Corbari and Mancini 2022).…”
Section: Application Of Technology To Estimate Crop Water Requirement...mentioning
confidence: 99%
“…Thus, it is a need to better estimate crop water requirements. Ippolito et al (2022) suggest a procedure to obtain highly accurate results on dynamics of soil water content and actual crop evapotranspiration under the investigated field conditions. Moreover, it highlights that site-specific crop coefficients, accounting for local and time-variable conditions in the field, can improve crop water requirement predictions, irrigation scheduling and thus, can also forward the implementation of precision irrigation strategies.…”
Section: Application Of Technology To Estimate Crop Water Requirement...mentioning
confidence: 99%
“…Numerous applications of the A&P approach to tree crops have been reported, e.g., by Paço et al [23] for peach; Paço et al [24] and Puig-Sirera et al [25] for olive; Vinci et al [26] for hazelnut; and Mobe et al [27] for various apple orchards in South Africa. Applications to vineyards include Williams et al [21], who reported on a survey of California vineyards, using A&P. The applications to citrus are also numerous [28][29][30][31][32]. These applications make us confident about the effectiveness of using the A&P approach.…”
Section: Introductionmentioning
confidence: 99%